Computerized order entry, clinical decision support, and safer prescribing. (August 2017) - Pontefract, S.K.; Ferner, R.E.
Abstract : Summary: Unintended harms from medicines caused by adverse drug reactions and medication errors are common. The medication process is very complex, and error can occur in the development, manufacture, distribution, prescribing, dispensing, administration, and monitoring of medicines. The prescriber, to avoid error, must first make careful decisions tailored to account for numerous factors that differ from patient to patient, then communicate orders that others must execute meticulously and whose consequences must be adequately monitored.